(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Do good, get good,is the new human resource management mantra. Every bit of the human resource ofany organization has to be respected and bestowed with befitting HRM practicesto generate service oriented behaviours for fantastic and phenomenal success inthe global tourism. So, this study has practical and policy implications forthe organizations, and service organizations in particular. Organizations cancertainly make significant improvements to their performance by emphasizingexcellent human resource management practices. Research papers, articles,newspapers, books, internet etc. are all flooded with dialogues onglobalization. In fact, it is no exaggeration. It is the catch word now-a day.The massive change in the style and structure of businesses has furtherstrengthened the belief that globalization is heading its way for even biggerdimensions and at an ever increasing pace. Economies are witnessing a new faceof competition. In a fast-paced, globally competitive economy, efforts to boostproductivity and quality never end (Cascio, 1998). The Indian governmentcompanies need to learn from the practices adopted by the private/multinationalcompanies especially with regard to competitive compensation, selection andsocialization of employees, and contemporary HR practices. Gone are the dayswhen experience was the basis for deciding seniority, which in turn was thebasis for deciding compensation.